RUIM – A fire safety engineering model for rural urban interface firefighter taskforce deployment. (May 2020) - Penney, Greg; Habibi, Daryoush; Cattani, Marcus
Abstract: Firefighting at the rural urban interface remains one of the most dangerous activities undertaken by fire services internationally. Whilst there is a significant volume of literature and describing methods for fire engineering safety analysis in the urban environment, a significant gap remains in the context of the rural urban interface. To address this, this article presents the Rural Urban Interface Model (RUIM). An adaptation of the Fire Brigade Intervention Model (FBIM), the RUIM enables systematic analysis of firefighter safety during catastrophic and dynamic wildfire events. When applied correctly, the RUIM provides additional guidance to Incident Controllers and Incident Management Teams regarding the suitability and safety of defensive firefighting strategies. Ultimately, the inclusion of the RUIM as part of operational fire ground analysis may reduce the potential for fatalities or injuries arising from firefighting taskforces being caught in wildfire burnover.